2019
DOI: 10.1002/pam.22158
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act's Effects on Patients, Providers, and the Economy: What We've Learned So Far

Abstract: As we approach the tenth anniversary of the passage of the Affordable Care Act, it is important to reflect on what has been learned about the impacts of this major reform. In this paper, we review the literature on the impacts of the ACA on patients, providers, and the economy. We find strong evidence that the ACA's provisions have increased insurance coverage. There is also a clearly positive effect on access to and consumption of health care, with suggestive but more limited evidence on improved health outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 107 publications
0
39
0
Order By: Relevance
“…In addition to having direct consequences for the targeted population, Medicaid expansions have the potential to generate indirect effects known as “welcome mat” effects, which occur when persons previously eligible for Medicaid, but not enrolled, sign up following coverage expansions to other populations. As summarized by Gruber and Sommers (2019), prior studies suggest that the ACA's Medicaid expansions significantly increased Medicaid participation by both children and working‐age adults who were previously eligible (e.g., Frean, Gruber, & Sommers, 2017; Hudson & Moriya, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having direct consequences for the targeted population, Medicaid expansions have the potential to generate indirect effects known as “welcome mat” effects, which occur when persons previously eligible for Medicaid, but not enrolled, sign up following coverage expansions to other populations. As summarized by Gruber and Sommers (2019), prior studies suggest that the ACA's Medicaid expansions significantly increased Medicaid participation by both children and working‐age adults who were previously eligible (e.g., Frean, Gruber, & Sommers, 2017; Hudson & Moriya, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Literature reviews conclude that the expansion led to significant increases in coverage and access to care for low-income individuals in expansion states. 1,2 The evidence on the effects of the Medicaid expansion on health, however, is less clear. While some studies document improvements in self-reported health, [3][4][5][6][7][8] cardiac health, 9 and survival from end-stage renal disease, 10 others find no significant improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous studies have investigated the effects of ACA‐Medicaid expansion on these outcomes using quasi‐experimental differences‐in‐differences (DD) methods. Of particular relevance to our study, while there is a vast literature investigating effects of ACA‐Medicaid expansion on health care service utilization generally, 18,19 few studies have estimated the causal effects of this major policy on breast cancer service use, and available studies focus on screening and surgeries with inconclusive results. Several studies find no change in breast cancer screening in expansion states vs nonexpansion states 20‐24 .…”
Section: Introductionmentioning
confidence: 99%